An innovative method to conduct temperature rise test on medium voltage switchgear assembly based on IEC standards in a power grid. Issue 1 (8th July 2022) - Iderus, Samat; Peter, Geno; Ganji, Vivekananda
Abstract: Modern civilization is characterised by a high need for electrical energy. The importance of electricity in daily life has grown to the point that it is desirable to safeguard the power system from damage during fault situations and to ensure maximum supply continuity, which necessitates the use of switchgear. Testing of any electrical equipment indicates the extent to which the equipment is able to comply with a customer's requirements. In this paper temperature rise test on a medium voltage switchgear assembly is considered. In this research, sub‐clause 6.5.2 of IEC standard 62271‐1 is followed to conduct temperature rise test on a medium voltage switchgear assembly. The test is conducted on two modes, first following the existing method of testing and second by an innovative method of testing. The temperature rise test is conducted on a 12 kV, 50 kA, 3150 A single busbar switchgear assembly and the readings are measured, analysed and compared between the two methods. It is concluded that the temperature rise recorded following the innovative method is more accurate compared to the existing method, as an increase in the recorded temperature rise is seen in all the thermocouple locations as the heat dissipation to the ambient is reduced.